High voltage engineering fundamentals - Kuffel, E. (Butterworth-Heinemann/Newnes, 2000)
Power transfer for large systems depends on high system voltages. The basics of high voltage laboratory techniques and phenomena, together with the principles governing the design of high voltage insulation, are covered in this book for students, utility engineers, designers and operators of high voltage equipment. In this new edition the text has been entirely revised to reflect current practice. Major changes include coverage of the latest instrumentation, the use of electronegative gases such as sulfur hexafluoride, modern diagnostic techniques, and high voltage testing procedures with stat.
Keywords: Electrical engineering.; High voltages.; Electric insulators and insulation.; Breakdown (Electricity); elektronické knihy; electronic books